Pancasila As A Philosophical Basis Of Law Formation In Indonesia - Vincentius Setyawan (PT. Islamic Research Publiser, 2023)
Abstract: The significance of legal philosophy in shaping Indonesian law is paramount, with Pancasila serving as the cornerstone of all legal foundations. Mandating that every Indonesian law must derive from Pancasila, it stands as the epitome of legal sources. As the bedrock of legislation and regulations in Indonesia, Pancasila emanates from the fundamental values ingrained in living law. Employing normative legal research methods and a conceptual legal approach, this article delves into the profound influence of Pancasila on the Indonesian legal framework. The findings underscore the colossal role of Pancasila as the philosophical underpinning of prevailing laws and regulations in Indonesia, exerting a substantial impact on the formulation of legal norms. Functioning as a spiritual principle within Indonesian law, Pancasila serves as the bedrock for constructing and shaping the entire Indonesian legal system. This study illuminates the pervasive influence of Pancasila, elucidating its intricate role in the intricate tapestry of Indonesia's legal landscape.